From Black Gold to Green Goals: Navigating Oil and Gas Sustainability - Yaghi, Racha (Journal of Ecohumanism, 2024)
The energy transition in the oil and gas sector is a complex but unavoidable journey. While the challenges faced by this sector are significant, the potential for innovation, collaboration, and sustainable growth remains vast. The urgent need for responsible energy policies is crucial to guarantee that energy production aligns with ecological preservation. This paper aims to critically examine the sustainability initiatives implemented by oil and gas companies within their energy policies, assess the international legal frameworks, and analyze national regulations governing the industry. A comprehensive review of existing literature and case studies of industry practices will be conducted to understand the effectiveness of current sustainability efforts. The findings will reveal successful initiatives and areas needing improvement, highlighting the interplay between regulatory frameworks and corporate practices. The study underscores the importance of strategically adopting sustainability measures in the oil and gas sector to mitigate environmental impact while enhancing economic growth. Recommendations will be provided for enhancing stakeholder collaboration and strengthening policy frameworks to support a more sustainable future in the energy landscape.